2020
DOI: 10.2174/1871523018666190401154447
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid A in Serum and Ascitic Fluid as a Novel Diagnostic Marker of Spontaneous Bacterial Peritonitis

Abstract: Background: Diagnosis of Spontaneous Bacterial Peritonitis (SBP) depends mainly on ascetic fluid culture which may be negative in spite of the clinical suggestion of SBP and high ascetic fluid neutrophilic count. Aim: This study aimed to evaluate the biological importance of amyloid A biomarker in both serum and ascetic fluid to diagnose SBP as early as possible and to compare it to other markers (C-reactive protein (CRP), and the neutrophil-to-lymphocyte ratio (NLR)). Methods: This study included 37 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…When the p value is closer to zero, the enrichment is more remarkable. SAA could be considered a potential marker of Takayasu arteritis, 28 spontaneous bacterial peritonitis, 29 hand, foot, and mouth disease, 30 and early infectious complications after laparoscopic surgery for colorectal cancer. 31 SAA has been reported as a known biomarker of AS for several years, 32,33 but we found that the area under the ROC curve of SAA was 0.604 for active vs stable AS, 0.707 for stable AS vs normal humans, and 0.718 for active AS vs healthy humans (Figure S4A).…”
Section: Discussionmentioning
confidence: 99%
“…When the p value is closer to zero, the enrichment is more remarkable. SAA could be considered a potential marker of Takayasu arteritis, 28 spontaneous bacterial peritonitis, 29 hand, foot, and mouth disease, 30 and early infectious complications after laparoscopic surgery for colorectal cancer. 31 SAA has been reported as a known biomarker of AS for several years, 32,33 but we found that the area under the ROC curve of SAA was 0.604 for active vs stable AS, 0.707 for stable AS vs normal humans, and 0.718 for active AS vs healthy humans (Figure S4A).…”
Section: Discussionmentioning
confidence: 99%
“…Serum Amyloid-A level has high sensitivity and specificity than ascitic fluid level. 15 A study conducted on patients having culture negative neutrocytic ascites mentioned that it is a variant of SBP and having mortality rate same as SBP. The term culture negative neutrocytic ascites was used in 1984 by Runyon and it is described as increased neutrophil count in ascitic fluid greater than 250 cells/mm 3 , negative ascitic fluid culture and absence of antibiotic therapy in last one month, no intra abdominal source of infection which can be treated surgically or pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…The area under the curve was 0.706 (95% confidence interval: 0.576-0.798). The procalcitonin level was significantly correlated with the (ascitic fluid) white blood cell count (rs=0.404, P<0.01) [20,37]. Cekin et al, reported higher procalcitonin serum levels in patients with positive bacterial culture in ascitic fluid compared to patients without culture positivity [21,38].…”
Section: Discussionmentioning
confidence: 99%